Entre dissonance et consonance : les multiples facettes de l’expérience du visiteur explorant l’art contemporain au musée - Anne-Marie Émond (Les Cahiers de l'École du Louvre)
The following is a synthesis of twenty years of research conducted in museum education on the psychological functioning of adult visitors exploring contemporary artworks. The identification of the dissonances and consonances expressed by visitors has allowed us to understand, among other things, the foci of attention as well as some of the mental operations that contribute to a transformative aesthetic experience. This article presents the factors that favour the participant-visitor’s relationship with contemporary art, one in which the adult is led to consider the pleasures of ambiguity and to appreciate the new experiences provoked by the works exhibited in a museum.